Edukasi Pencegahan Diare melalui Perilaku Hand Wash pada Anak Sekolah Dasar SD 9/IV Kota Jambi - Armina Armina; Ratu Kusuma (Jurnal Abdimas Kesehatan (JAK), 2021)
The incidence of diarrhea is often experienced by children. Based on Riskesdas data, during 2018 there were 12.3% cases of diarrhea in Indonesia. Jambi province cases of incidence in children are about 8.6% based on health profile data in 2017 the coverage of handling diarrhea in children reaches 43.79% which exceeds the target for handling diarrhea, which is 10%. Diarrhea in school-age children can be caused by an unsanitary environment, snacking habits at school and rarely washing hands. Based on observations at SD 9/IV Jambi City, there were food vendors in front of the school, beside the SD there were trash bins and were large enough that they looked unclean where this could create a bad smell for the elementary school children and there were many food vendors in front of the school. Elementary school makes children often buy these foods. Therefore, the service team is interested in conducting counseling with the title of diarrhea prevention with hand washing behavior at SD 9/IV Jambi City. The service was carried out in June 2020. The service was carried out in the form of counseling. Based on the results of the service, children of primary school age experienced an increase in knowledge about diarrhea prevention and experienced an increase in hand washing. The results of this service are expected that the children of SD 9/IV Jambi City are able to prepare to wash their hands before eating or snacking while at school and even at home.